«OLD WOMAN IN VERY MODERN INTERNATIONAL DRESS» (GERMAN DUAL SYSTEM OF VET IN GERMANY AND IN THE WORLD) - Dr. Kress Hannelore; Ekaterina Y. Esenina (Russian State Vocational Pedagogical University, 2015)
The purpose of authors - the colleagues cooperating within the Russian-German working group on vocational education - is to determine features of the German dual system of vocational education and training (VET) which make it effective and popular not only in Germany, but also in the world.Methods. In the presented article the methodology of comparative research on the basis of the analysis of results of activity of Slovakia, Italy, South Korea, Russia and other countries on reforming of VET system on the basis of experience of Germany is used. Methods of collecting empirical information on the projects started in the specified countries, methods of the conceptual and terminological analysis, interpretation and modeling, a problem method are chosen.Results. Specifics of the German dual system are revealed; the generalized model of dual VET is constructed; features of approaches of the different countries to use positive experience of Germany for development of its own VET systems are characterized.Scientific novelty. The authors point out the consecutive justification of the conditions necessary for quality vocational education in modern market economy relying on results of the comparative analysis of reforming processes of VET systems in different countries.Practical significance. Need of public-private partnership as bases of quality of personnel preparation and ensuring economic competitiveness of the countries is shown and concrete ways of creation of such partnership in a number of the Russian regions are described. The experience presented above can be used throughout the Russian Federation.